Integration Policies, Diversity Management and Guarantee of Rights in the “Cities for Change”: The Case of Barcelona, València and Madrid - Mora Castro, Albert (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
After the local elections of 2015, new left-wing parties and municipal confluences, linked to the 15-M movement, came to power in the main Spanish cities breaking the traditional dynamics of power in the Spanish local political system. This paper analyzes the integration and coexistence policies that these governments carried out between 2015 and 2019, the principles that guided them, the most relevant measures and the main transformations that were produced in this field. Mainly through qualitative interviews with policy makers, practitioners and civil society representatives, it is showed how the local governments can work to create more inclusive cities that are based on the principles of interculturalism and human rights. The case of Barcelona stands out as the one in which the transformations have been more significant.